USING A SLEDGEHAMMER TO CRACK A NUT: THE SCOPE AND POWERS OF THE MINE HEALTH AND SAFETY INSPECTORATE IN LIGHT OF Anglogold Ashanti Ltd v Mbonambi (2017) 38 ILJ 614 (LC) - C Tshoose; B Khumalo (Obiter, 2018)
This case note examines the scope of the MHSI’s powers to issue section 54(1) instructions and the circumstances under which these instructions should be issued. Furthermore, the note examines the relevant jurisprudence of the South African courts dealing with the review of the MHSI’s exercise of power both in imposing administrative fines and issuing mine stoppage orders. This is done in light of the decision in AngloGold Ashanti. The note shows the importance of section 54 instructions and the role they have played in the reduction of serious injuries and fatalities at the mines over the past two decades. Nevertheless, the MHSI’s exercise of power in terms of the provision is not immune from critique. The facts of the case are outlined below. This is followed by a few comments and then a conclusion is drawn. The terms “employer” and “mining company” are used interchangeably in this contribution.